THE ORGANISATION OF THE ESTABLISHMENT OF THE QUALITY CONTROL SYSTEM IN A READY WEAR COMPANY PRODUCING CLASSICAL MEN TROUSERS - (:unkn) unknown (EGE UNIVERSITESI, 2009)
Nowadays, for apparel companies to compete in national and international markets, they have to satisfy the expectations of the customers in terms of time, cost and quality. Especially, fast fashion concept in marketing and shopping, require the products to be delivered in four or six months by producer. In addition, classical manufacture approaches have become absolute due to production numbers decrease and models increase. In place of this, flexible manufacture approach accepted where sewing whole models of one product are seen. All these developments made necessary for apparel companies to prosecute the quality assurance concept. In this study, systematically quality control model was proposed for classical man pants production for apparel industry to make quality production and provide continuity. In this direction, observation and analysis was carried out of company and mistakes are prevention for mechanism offered not repeating the mistakes over again. Quality control cards prepared and put into practice to perceive easily by all workers. Results of the applications have shown decrease on Faulty products and continuity at quality product.
Keywords: Classical man trousers; Quality assurance; Quality control system; Quality control card; Visual control